Determinants of recovery from a 161-km ultramarathon. Issue 7 (3rd April 2017) - Hoffman, Martin D.; Badowski, Natalie; Chin, Joseph; Stuempfle, Kristin J.; Parise, Carol A.
ABSTRACT: The primary study objective was to identify determinants of short-term recovery from a 161-km ultramarathon. Participants completed 400 m runs at maximum speed before the race and on days 3 and 5 post-race, provided a post-race blood sample for plasma creatine kinase (CK) concentration, and provided lower body muscle pain and soreness ratings (soreness, 10-point scale) and overall muscular fatigue scores (fatigue, 100-point scale) pre-race and for 7 days post-race. Among 72 race finishers, soreness and fatigue had statistically returned to pre-race levels by 5 days post-race; and 400 m times at days 3 and 5 remained 26% ( P = 0.001) and 12% ( P = 0.01) slower compared with pre-race, respectively. CK best modelled soreness, fatigue and per cent change in post-race 400 m time. Runners with the highest CKs had 1.5 points higher ( P < 0.001) soreness and 11.2 points higher ( P = 0.006) fatigue than runners with the lowest CKs. For the model of 400 m time, a significant interaction of time with CK ( P < 0.001) indicates that higher CKs were linked with a slower rate of return to pre-race 400 m time. Since post-race CK was the main modifiable determinant of recovery following the ultramarathon, appropriate training appears to be the optimal approach to enhance ultramarathon recovery.